2021
DOI: 10.3390/catal11080993
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Assessment of Catalytic Performances of Mn2O3 Nanoparticles for Peroxymonosulfate Activation during Bisphenol A Degradation

Abstract: Catalytic performances of Mn2O3 nanoparticles for peroxymonosulfate (PMS) activation in bisphenol A (BPA) degradation were comprehensively investigated in this study. Experimental results showed that 10 mg/L BPA could be 100% degraded within 20 min with the dosages of 0.2 g/L Mn2O3 and 0.1 mM PMS. Moreover, Mn2O3 showed remarkable activity in activation of PMS and excellent adaptability in various real water matrices, including river water, tap water and secondary effluents. Based on the radical detection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…29,38,39 Remarkably, 1 O 2 could also be formed through the reaction of HSO 5 − and O* converted from O L , as eqn (24) and (25) described. 36 Finally, MB molecules were attacked and degraded by these reactive radicals (SO 4 ˙ − , ˙OH and ˙O 2 − ) and non-radicals ( 1 O 2 ). The proposed degradation mechanism for MB in the integral NF-based Co 3 O 4 /PMS system is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29,38,39 Remarkably, 1 O 2 could also be formed through the reaction of HSO 5 − and O* converted from O L , as eqn (24) and (25) described. 36 Finally, MB molecules were attacked and degraded by these reactive radicals (SO 4 ˙ − , ˙OH and ˙O 2 − ) and non-radicals ( 1 O 2 ). The proposed degradation mechanism for MB in the integral NF-based Co 3 O 4 /PMS system is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…29,38,39 Remarkably, 1 O 2 could also be formed through the reaction of HSO 5 À and O* converted from O L , as eqn ( 24) and ( 25) described. 36 Finally, MB molecules were attacked and degraded by these reactive radicals (SO 4 À , OH These findings suggested that the integral NF-based Co 3 O 4 was a promising candidate catalyst for activating PMS to remove organic contaminants owing to its excellent catalytic efficiency, high stability and easy recovery feature.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…Cobalt (Co)-based catalysts have been reported as the most efficient catalyst in PMS activation to generate SO 4 •− [10]. To date, a numerous of Co containing materials as heterogeneous catalyst have been studied as PMS activators.…”
Section: Introductionmentioning
confidence: 99%